PERSEPSI MASYARAKAT TERHADAP EMPAT PILAR KEBANGSAAN DI KAMPUNG AGUNG JAYA - Budi Cahyanto; Holilulloh Holilulloh; Mohamad Mona Adha (FKIP Unila, 2013)
Based on the result of data analysis, it was found that citizen’s perception toward four nationality pillar in Kampung Agung Jaya Kecamatan Banjar Margo Kabupaten Tulang Bawang is not quite good. That thing can be explained as following : 1. The citizen’s perception toward four nationality pillar in term of cognitive indicator is categorized is not quite know. 2. The citizen’s perception toward four nationality pillar in term of respond indicator is categorized is not quite do. 3. The citizen’s perception toward four nationality pillar in term of opinion indicator is categorized is not quite agree.Berdasarkan hasil analisis data dapat diketahui bahwa persepsi masyarakat terhadap empat pilar kebangsaan di Kampung Agung Jaya Kecamatan Banjar Margo Kabupaten Tulang Bawang adalah kurang baik. Hal tersebut dapat dijelaskan sebagai berikut: 1. Untuk persepsi masyarakat terhadap empat pilar kebangsaan indikator pengetahuan (kognisi) dikategorikan kurang baik. 2. Untuk persepsi masyarakat terhadap empat pilar kebangsaan indikator tanggapan dikategorikan kurang baik. 3. Untuk persepsi masyarakat terhadap empat pilar kebangsaan indikator pendapat dikategorikan kurang baik.Kata kunci: empat pilar kebangsaan, masyarakat, persepsi